Syntactic Variability in Spoken English Discourse through Age Dimensions - Velyan, Karen (Armenian Folia Anglistika, 2012)
The present article demonstrates certain syntactic expressions of the informal spoken English discourse among native speakers belonging to different age groups. The data of our analysis demonstrate that the frequency of the application of linguistic variables differs among different age categories of native speakers. This is particularly expressed in the frequency of the use of English conjunctions and and but in terms of the frequent use of attributive clauses and adverbial clauses with because.